Reimagining node: a proposal for pop-up urbanism initiative in Alor Setar / Sayed Muhammad Aiman Sayed Abul Khair ... [et al.] - Sayed Abul Khair, Sayed Muhammad Aiman; Yuserrie, Farid Al Hakeem; Zainal Abidin, Mohammad Nazrin; Husain, Fazidah Hanim; Mohamed Noor, Nur Azdli (Universiti Teknologi MARA, Perak, 2024)
A big part of tactical planning is pop-up structures. As part of a secondyear architecture design lab, this study looks at pop-up urbanism in the city centre of Alor Setar, focussing on short-term changes that make places lively and focused on people. In line with Alor Setar's Strategic Plan 2024–2028, the study aims to make cities better places to live by using strategic popup buildings. A mixed-method approach combines Edward T. White's Site Analysis with the Space Syntax method. It starts with finding important places like Dataran Alor Setar. A lot of site data is being collected and analysed for the study to determine how cities change over time. Space Syntax helps determine how to connect and integrate spaces, which helps with where to put these temporary changes. Key results show that areas with a lot of connections, like Jalan Istana Lama and Lebuhraya Darul Aman II, are great for making things livelier, whilst areas with fewer connections, like Lebuhraya Darul Aman I, are better for targeted interventions. The study gives useful information to students who are designing pop-up structures. It also helps with future urban planning, which makes cities more resilient and open to everyone.